2015
DOI: 10.1080/13102818.2015.1066234
|View full text |Cite|
|
Sign up to set email alerts
|

Histopathological evaluation of gingival tissue overlying two-stage implants after placement of cover screws

Abstract: Corrosion of implant components, including that of cover screws, has been reported as a possible etiological factor for implant failure. This study evaluated the presence of metallic particles in the soft tissues overlying two-stage implants after placing cover screws, by using a histological technique and energy-dispersive X-ray spectroscopy. The results showed large and small titanium particles in different layers of the soft tissue overlying the implant and cover screws in the majority of samples, with more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Olmedo and co-workers[ 20 ] studied and detected Ti in soft tissues by EDX analysis. Paknejad and co-workers[ 21 ] studied biopsies of 96 subjects implants by EDX. They reported the existence of a correlation between the Ti ions and inflammation of the soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Olmedo and co-workers[ 20 ] studied and detected Ti in soft tissues by EDX analysis. Paknejad and co-workers[ 21 ] studied biopsies of 96 subjects implants by EDX. They reported the existence of a correlation between the Ti ions and inflammation of the soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with a study by Olmedo and co-workers [28] that detected titanium particles by EDX analysis in soft tissues associated with 10 implants explanted because of clinical mobility. Paknejad and co-workers [29] studied biopsies from 96 patients treated with two-stage approach implants by EDX and reported that all samples presented with a high density of large titanium particles. They concluded from their investigation that there was a correlation between the presence of titanium particles and the level of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…79 Two studies have focused on the evaluation of the Ti release from cover screws of endosteal implants to adjacent gingival tissues, and both showed this phenomenon. 80,81 Mercan et al 80 reported an almost 1.4-fold elevation in the titanium content in gingiva in comparison with the control group in a relatively short time (3 months). Metallic debris can migrate throughout the different layers of the peri-implant soft tissues, as observed by Paknejad et al 81 Mild and moderate inflammations were observed, respectively, in 65.6% and 33.3% of the samples from the epithelium-connective tissue junction, while mild, moderate This journal is © The Royal Society of Chemistry 2016 and severe inflammatory responses were detected in, respectively, 59.4%, 33.3% and 5.2% of the samples from the connective tissuecover screw surface junction.…”
Section: Dental Implantsmentioning
confidence: 98%